Analisis Proses Formulasi Peraturan Daerah (Studi Pada Peran DPRD Lombok Barat Dalam Proses Formulasi Perda No 3 Tahun 2015 Tentang Pedoman Umum Pelaksanaan Pengarusutamaan Gender Dalam Pembangunan Di Kabupaten Lombok Barat) - Mustamin H. Idris; Rahmad Hidayat; Mahsar Mahsar (JIAP (Jurnal Ilmu Administrasi Publik), 2018)
Reform and regional autonomy are under way in the country and are expected to provide a more democratic life. One of them is the demands of the Regional People's Legislative Assembly (DPRD) to carry out its duties and functions in the regions, the wrong function of legislation, the formulation process of Regional Regulation (PERDA). The purpose of this study is intended to examine the role of the West Lombok Regional House of Representatives as one of the actors of Policy Formulation of PERDA. 3 of 2015 on General Guidelines of Gender Mainstreaming in Development in West Lombok Regency and the Factors Affecting it. The method used in this research is qualitative method with descriptive approach, the data in this research are primary and secondary data in the form of observation, interview and documentation. The results of this research indicate that the role of West Lombok Regency DPRD as one of the actors of PERDA Formulation is seen from its role in the drafting of Local Regulation, where most have been run in accordance with Standard Operating Procedures (SOP), following the procedure of drafting of Raperda and preparing Raperda. Other actors involved are Family Planning and Women Empowerment (BKBPP). Supporting Factors are in the form of budget as a form of support from the budget of APBD for the field of women's empowerment, facilities and infrastructure formation Raperda Initiative DPRD. While the inhibiting factor in the formation of Raperda Initiative is Human Resources (HR) Experts remain that are not yet available in the formulation of Raperda on Gender Mainstreaming.